The Significance and Application of Maqashid Sharia in Contemporary Economic Practices: A Qualitative Analysis - Isnaini Isnaini; Bayu Sugara (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
This study delves into the meaning of Maqashid Sharia (the objectives of Islamic law) within the context of the economy, aiming to elucidate its significance and application in contemporary economic practices. Maqashid Sharia, which encompasses preserving religion, life, intellect, progeny, and wealth, is a comprehensive framework guiding ethical and equitable economic behavior. This research employs a qualitative approach, analyzing primary Islamic sources—the Quran and Hadith—as well as scholarly interpretations to uncover the economic implications of Maqashid Sharia. The study highlights that Maqashid Sharia promotes a balanced economic system that prioritizes social welfare and justice, ensuring that economic activities contribute to society's overall well-being. Key principles derived from Maqashid Sharia include the prohibition of riba (usury), the importance of zakat (almsgiving), and the encouragement of fair-trade practices. These principles are designed to prevent exploitation, reduce poverty, and ensure wealth distribution among all societal members. Furthermore, the research explores contemporary applications of Maqashid Sharia in Islamic finance and banking, emphasizing how these institutions strive to align their operations with Islamic objectives. The findings reveal that incorporating Maqashid Sharia into modern economic systems can lead to more sustainable and socially responsible economic practices. This study contributes to the broader understanding of Islamic economics by providing insights into how Maqashid Sharia can be effectively integrated into modern economic policies and practices, promoting an ethical and equitable economic order in line with Islamic values.